The financial impact on the growth of Solvay with the acquisition of Cytec Industries, inc. - Santos, João Gonçalo Ferreira (2019)
This project is presented upon a form of a case study, and the goal is to evaluate the impact on the financial growth of Solvay with the acquisition of Cytec Industries, Inc and make a possible prediction in the financial results of future years of Solvay that is directly related to the acquisition itself. To achieve this objective, it is carried a theoretical bibliographic revision on the theme of merger and acquisitions to explore in depth the concepts and all the processes from the beginning to the end of a merger and acquisition. The main concepts will be related to the main reasons of why firms choose to merge or acquire another company, as well as their advantages, disadvantages, process of negotiation and evaluation forms. Once that chapter is finished, the case study begins, where it is presented the reasons of why Solvay decided to acquire Cytec, the negotiation phases and naturally the values involved. In order to have a general knowledge about both firms, a wide description of the businesses of both companies is presented, as well as their main financial transactions 2 years prior the acquisition. After that information, it is presented the calculations that will determine if the acquisition did in fact brought value to Solvay, and to do that, it will be used the financial data provided by Solvay up to 3 years after the acquisition. Furthermore, and to conclude this project, the final chapter is going to be a conclusion regarding the value of this acquisition, in which the acquisition did in fact added value to Solvay and the prediction is that in future years it will keep this pace.